BORYSLAV REGION’S MINERAL WOTERS USE FOR PATIENT’S REHABILITATION - Dudchenko, M.A.; Sorokina, S.I.; Третяк Н. Г. (World of Medicine and Biology, 2017)
The best rehabilitation remedy of the patients with kidney and digestive system diseases is a spa treatment. Carpathian has a natural resource for the development of climatic and spa resorts, with well known mineral wells such as the unique mineral water "Naftusya". On the basis of these wells there is a Truskavets resort more than 500 years exists. In connection with the mineral water " Naftusya" needs and lack the ability to debit the main mineral spring in the resort not enough investigate the "Naftusya"-like well is used. In this regard there is necessary to organize the Carpathian Health Resort Institute for the study of natural healing Carpathion capabilities and on their basis to develop a resort network in the region to ensure the needs in the treatment and rehabilitation of patients.
Keywords: Carpathian; spa treatment; "Naftusya"; Health Resort Institute